2012
DOI: 10.1111/j.1743-6109.2011.02502.x
|View full text |Cite
|
Sign up to set email alerts
|

Peyronie’s Disease in Teenagers

Abstract: Introduction Peyronie’s disease (PD) is commonly seen in middle-aged men, and little is known about this condition in teenagers. Aim To investigate the characteristics of PD in teenagers. Methods The findings were compared between patients with the disease who were teenagers with those over 40 years of age. Statistical analyses were conducted to define differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 28 publications
1
35
1
3
Order By: Relevance
“…Several studies have reported about 5% to 10% of patients present with PD who are <40 years of age [32–34]. A recent study has demonstrated that PD can also occur in a teenage patient population, and it is generally associated with high levels of distress in this population [35]. It is conceivable that future studies may need to consider age as a variable when examining PD symptoms such as bother and distress.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported about 5% to 10% of patients present with PD who are <40 years of age [32–34]. A recent study has demonstrated that PD can also occur in a teenage patient population, and it is generally associated with high levels of distress in this population [35]. It is conceivable that future studies may need to consider age as a variable when examining PD symptoms such as bother and distress.…”
Section: Discussionmentioning
confidence: 99%
“…17, 18 Despite the higher incidence in older men, PD can affect men of all ages, from teenagers to men over 70 years old. 1921 Reported prevalence rates of PD range from 0.4% to 13%, although these are likely underestimates due to an under-reporting bias; men are often reluctant to discuss this condition. 21, 22 …”
Section: Epidemiologymentioning
confidence: 99%
“…The potential importance of testosterone deficiency, hypertension, dyslipidemia, and diabetes mellitus is indicated by preliminary studies suggesting an association between these conditions and increased risk for or severity of Peyronie's disease (Cavallini, Biagiotti, & Lo Giudice, 2012;El-Sakka, 2006;El-Sakka et al, 2005;Kadioglu et al, 2002;Nam, Park, & Park, 2011;Rhoden, Riedner, Fuchs, Ribeiro, & Halmenschlager, 2010;Tal et al, 2012;Tefekli, Kandirali, Erol, Tunc, & Kadioglu, 2006). The potential importance of testosterone deficiency, hypertension, dyslipidemia, and diabetes mellitus is indicated by preliminary studies suggesting an association between these conditions and increased risk for or severity of Peyronie's disease (Cavallini, Biagiotti, & Lo Giudice, 2012;El-Sakka, 2006;El-Sakka et al, 2005;Kadioglu et al, 2002;Nam, Park, & Park, 2011;Rhoden, Riedner, Fuchs, Ribeiro, & Halmenschlager, 2010;Tal et al, 2012;Tefekli, Kandirali, Erol, Tunc, & Kadioglu, 2006).…”
Section: Discussionmentioning
confidence: 99%